Peritoneal sedal drains - Praderi, Raúl (Cirugía del Uruguay, 1978)
Report on a new procedure for peritoneal drainage by means of a thick tube laterally perforated and connected by its end to a thin plastic tube system which serves as air intake or for washing purposes if serum is injected into it using pressure. These drains are always permeable and may by withdrawn by, isplacing them outwards and placed back in position means of the washing tube which guides them into place.